Association of Estrogen Receptor 1 PvuII and XbaI Polymorphisms and Peripheral Estrogen Receptor 1 mRNA Levels with Alzheimer's Disease in Turkish Patients - Gamze Güven; Pınar Köseoğlu Büyükkaya; Melisa Kılıç; Damla Uzun; Betül Cavuş; Filiz Güçlü Geyik; Ebba Lohmann; Bedia Samancı; Hakan Gürvit; Hasmet Hanağası; Başar Bilgiç (Türk Nöroloji Dergisi, 2023)
Objective: Estrogen receptor 1 (ESR1) polymorphisms are associated with Alzheimer's disease (AD) and polymorphisms in the first intronic region of the gene are known to affect ESR1 mRNA transcription. The first intronic region of the ESR1 contains two polymorphisms that have received the most attention: PvuII rs2234693 (NM 000125.3: c.453-397T>C) and XbaI rs9340799 (NM 000125.3: c.453-351A>G). Both polymorphisms have been shown to be associated with AD, but consistent findings across populations have not been established. This study aimed to determine whether ESR1 PvuII and XbaI polymorphisms are associated with the disease in a cohort of Turkish AD patients. Whether PvuII and XbaI polymorphisms affect disease susceptibility by influencing ESR1 mRNA expression was also examined. Materials and Methods: Genotyping was performed in 424 patients with AD (mean age: 64.5 +- 11.1 yrs) and 302 controls (mean age: 56.4 +- 13.0 yrs). The polymerase chain reaction (PCR) and restriction enzyme digestion methods were used to determine the prevalence of the ESR1 PvuII and XbaI polymorphisms. The ESR1 mRNA expression was analyzed in the peripheral blood cells of 85 patients and 53 age-matched controls using quantitative real-time PCR. Results: No significant difference in genotype and allele frequencies of ESR1 PvuII and XbaI polymorphisms between the patients and controls was found. However, the frequencies of the PvuII C and XbaI G alleles were significantly higher in the patients with the apolipoprotein-E (APOE) ε4 allele. The ESR1 mRNA levels were significantly lower in the patients with AD compared with the controls (P = 0.001). The XbaI A allele was significantly associated with lower ESR1 mRNA levels (P = 0.044) and this association remained significant even after adjusting for confounders such as age, gender and APOE ε4 carrier status (P = 0.035). Conclusion: This study demonstrated that the distribution of PvuII and XbaI alleles is associated with the APOE ε4 allele. The XbaI polymorphism may be associated with a higher risk of AD by altering ESR1 mRNA levels.